Perfil de sensibilidad y fenotipos de resistencia de Escherichia coli asociados a infecciones urinarias en pacientes atendidos en el Hospital Belén de Trujillo de enero a setiembre, 2018 - BACILIO PÉREZ, Héctor Daniel (2019)
Were determined the sensitivity profile and resistance phenotypes of Escherichia coli associated with urinary infections in patients treated at Belén de Trujillo Hospital from January to September, 2018. Different urine samples were processed during that period; E.coli culture colonies were inoculated into MicroScan ® panels for identification and automated sensitivity study. The following classification was used to establish the resistance phenotype associated with beta-lactams; enicillin-producing strains: resistance to ampicillin and preserved sensitivity to amoxicillin-clavulanic acid and the rest of the cephalosporins studied; Penicillinase hyperproducers: ampicillin resistance, decreased resistance or sensitivity to amoxicillin-clavulanic acid and decreased sensitivity or resistance to cefuroxime; Amp C: resistance to ampicillin, amoxicillin-clavulanic acid, cefoxitin and the rest of the cephalosporins studied. In the strains with suspected phenotype of BLEE or Carbapenemasas production, confirmation was made using the manual method. The data obtained were processed and analyzed through the SPSS24 program; grouped into categories and expressed through distribution of frequencies and percentages according to the objectives. High levels of resistance of E. coli to cephalosporins and fluoroquinolones were found. Of the resistance phenotypes analyzed, BLEE strains were the most frequent (39.3%). The antibiotics with the highest activity against E.coli were ampicillin, nitrofurantoin, fosfomycin and piperacillin-tazobactam with less than 20% resistance;Therefore, these antimicrobials are a valid option for the empirical treatment of urinary tract infection in patients treated at Hospital Belén de Trujillo.